A review on substitution of natural sand with granite fines in sustainable concrete - Li, Ziyang (2023)
A mass amount of granite fine (GF), a byproduct of the cutting and grinding process in the masonry industry, is generated every year all around the world. Most of these wastes are landfilled which will cause serious environmental problems. The usage of GF as the sand substitution in concrete may ideally not only help minimize the environmental issues but also provide economic benefit. Due to significant variations on the properties of the material being used and different understanding of GF substitutional concrete existing among different researchers based on their experimental works and local material sources, a more conclusive and reconciled understanding should be established to improve industrial stakeholders’ confidence in applying this material for construction. In this paper, the laboratory tests and findings from various latest research papers and industrial reports are gathered to shed light on the effects of GF on the performance of concrete as natural sand (NS) substitute. Comprehensive reviews of GF concrete on the fresh property (e.g., slump, bleeding), hardened property (e.g., compressive strength, flexural strength, splitting tensile strength) as well as the durability (e.g., water permeability, water absorption, resistance to sulfate attack, and acid attack, carbonation, and chloride permeability) are presented. A comparative life cycle impact assessment study of four concrete mixes with different GF replacement levels is conducted by considering the cradle-to-gate boundary for the Singapore scenario. The results turn out that around 20% environmental impact reduction can be realized via the replacement of 25.6%−50% NS with GF.